Contribution à la commande robuste de la machine asynchrone à double étoile - HADJI, Chaabane (Université de M'sila, 2020)
This work is the contribution to the improvement of the control of the dual star asynchronous machine based on the technique of the field oriented control, fed by two voltage inverters. Indeed, initially, we carried out a general recall on the control of asynchronous machines with double star . Then we have interested in the regulation of the speed by the impact of replacement of regulator PI by other regulators based on MRAC regulators, sliding mode of order two, and in particular by Backstebbing. To validate and test the complete system (DSIM, the various regulators) a study of simulation under Matlab environment were also performed by several tests of simulation such as: unloading start, insertion of an external disturbance, load operation and reversing the direction of rotation, robustness tests for DSIM parametric variation, for various regulators. Moreover, in terms of obtained results, we can confirm the well dynamic performance and robustness to the external disturbance and parameter variations of the machine
Keywords: Double star induction machine DSIM; MRAC control; Sliding mode; Backstepping; Robust control.